AB0927 Probability and impact of achieving low disease activity or remission in patients with psoriatic arthritis treated with apremilast: pooled analysis of the palace 1–3 phase 3 trials. (12th June 2018) - McInnes, I.; Mease, P.J.; Behrens, F.; Orbai, A.-M.; Brunori, M.; Teng, L.; Guerette, B.; Smolen, J.
Abstract : Background: Baseline (BL) disease characteristics and short-term response status and its implications for long-term achievement of low disease activity (LDA) or remission (REM) in pts with active psoriatic arthritis (PsA) treated with apremilast (APR) are unknown. Objectives: 1) To assess BL clinical Disease Activity for Psoriatic Arthritis (cDAPSA) levels associated with achieving cDAPSA LDA or REM at Week 52 (Wk52); 2) predict cDAPSA response categories at Wk52 based on BL or Wk16 cDAPSA; 3) assess disease activity in different PsA domains associated with cDAPSA categories at Wk52. Methods: Pooled analyses (PALACE 1–3) were performed of pts assigned to receive APR 30 mg BID (APR30) at BL who completed Wk52 and had cDAPSA components available to calculate responses. Pts were grouped according to the cDAPSA categories reached at Wk52 (REM ≤4; LDA>4−≤13; MDA>13−≤27; HDA >27). Shifts of cDAPSA response categories from BL, Wk16 to Wk52 were reported and provided the predictability of BL status or early response to the achievement of cDAPSA categories at Wk52. Mean disease activity in core PsA domains, including swollen (0–76)/tender joint (0–78) (SJ/TJ), enthesitis (MASES), dactylitis count, Patient Global Assessment of Disease Activity (PtGA), Patient Assessment of Pain (PAP), Psoriasis Activity Severity Index (PASI), and Physical Function (HAQ) were reported longitudinally, allocated by cDAPSA category at Wk52. To better describe predictors associated with pts potentially being considered for APR in routine clinical practice, analyses were repeated removing pts in HDA at BL. Results: 374 APR30 pts were included in the analyses. Pts who achieved MDA, LDA or REM at Wk52 indicated sustained improvements in cDAPSA over time; Means of BL cDAPSA scores≤41 were associated with achievement of MDA, LDA and REM at Wk52 (figure 1). At BL, pts in HDA had 42%, 24% and 5% chances of achieving MDA, LDA or REM at Wk52, respectively. Pts in MDA at BL had 41% and 12% chances of achieving LDA or REM. Pts in LDA had 20% chances of achieving REM. At Wk16, pts in HDA had 43%, 8% and 1% chances of achieving MDA, LDA or REM. Pts in MDA had 38% and 2% chances of achieving LDA or REM. Pts in LDA at BL had a 20% chance of achieving REM and pts in REM a 67% chance of staying in REM. Achieving cDAPSA LDA or REM with APR at Wk52 was associated with residual disease activity as follows: SJ (1.2 vs. 0.24); TJ (2.6 vs. 0.52); MASES (1.2 vs. 0.43); dactylitis (0.47 vs. 0); PtGA (28.0 vs. 7.7); PAP (25.1 vs 7.2); PASI (4.0 vs. 2.7); HAQ (0.62 vs. 0.14). Removing pts with HDA at BL suggested that a mean cDAPSA 21 was associated with achieving LDA or REM at Wk52, corresponding to 5.5 in mean SJC and 9 in mean TJC at BL. Conclusions: Chances of achieving LDA or REM were greater for pts in MDA at BL or Wk16 vs. HDA. Achieving LDA or REM at Wk52 with APR was associated with good outcomes across core PsA domains. Results suggest that pts with BL moderate cDAPSA disease activity may be particularly suitable for APR therapy. Disclosure of Interest: I. McInnes Grant/research support from: Celgene, Abbvie, Pfizer, BMS, UCB, Roche, Janssen, P. Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Genentech, Janssen, Eli Lilly, Novartis, Pfizer, Roche, UCB, Consultant for: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Genentech, Janssen, Eli Lilly, Novartis, Pfizer, Roche, UCB, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Genentech, Janssen, Eli Lilly, Pfizer, UCB, F. Behrens: None declared, A.-M. Orbai: None declared, M. Brunori Employee of: Celgene Corporation, L. Teng Employee of: Celgene Corporation, B. Guerette Employee of: Celgene Corporation, J. Smolen Grant/research support from: Abbvie, Janssen, Lilly, MSD, Pfizer, Roche, Speakers bureau: Abbvie, Amgen, Astra-Zeneca, Astro, Celgene Corporation, Celtrion, Glaxo, ILTOO, Janssen, Lilly, Medimmune, MSD, Novartis-Sandoz, Pfizer, Roche, Samsung, Sanofi, UCB